2015
DOI: 10.4172/2161-0665.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Drop-Out between Tuberculosis and Measles Immunization among Infants in Parakou (Benin) in 2012

Abstract: Introduction: In Benin, the epidemiological profile is dominated by endemic and epidemic diseases preventable through immunization. This study had been carried out to determine the factors associated with the rate of drop-out between tuberculosis and measles immunization among infants aged 12-23 months in the District of Parakou. Methods: A descriptive cross-sectional and analytical study had been carried out from July to August 2013 on 510 couples of children-mothers of children aged 12 to 23 months in the Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
1
Order By: Relevance
“…In fact this might be due to missed appointment date and lack of awareness by caretakers for the scheduled date by health facility. More over this report is higher than finding in n Basra 19.3% [11], Haryana India, 13.88% [12] and Arba Minch 11.7% [13]. This might be due to access to immunization service, and EPI implanting plane different from one area to others.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In fact this might be due to missed appointment date and lack of awareness by caretakers for the scheduled date by health facility. More over this report is higher than finding in n Basra 19.3% [11], Haryana India, 13.88% [12] and Arba Minch 11.7% [13]. This might be due to access to immunization service, and EPI implanting plane different from one area to others.…”
Section: Discussioncontrasting
confidence: 62%
“…In Ethiopia, 70-80% of children received BCG initially, however 50-54% of them received end measles containing vaccine on schedule [5,6]. Many peer reviewed research on immunization dropout rate indicated that socio-economic and demographic factor, difficult on topography, armed conflict, maternal knowledge are factors that affect the completion of childhood immunization [7][8][9][10][11].…”
Section: Independent Factors Associated With Immunization Dropoutmentioning
confidence: 99%